Rhodopsin and retinitis pigmentosa - Kaushal, Shalesh (Henry Stewart Talks, 2007)
Anatomy of the eye and retina, Retinal degenerations, Retinitis pigmentosa, Protein conformational disorders, Model for disease, The study of mutant opsin, Structure of rhodopsin, Phenotypes, Class I, Class II and Class III mutants, Pharmacological chaperones, Can small molecules slow retinal degeneration in mouse models?
Archived at 2016/06/08